Study on the Anti Scuffing Performance of Gear based on Tooth Flank Phosphate - Xuhu Wang; Dongfei Wang; Lü Pangong; Chengtian Ma; Xiaopeng Dou; Yankun Zhang (Jixie chuandong)
The unphosphorized and phosphatized spur gears produced in the same batch are divided into three groups，the unphosphorized gear group， the single phosphated gear group and the double phosphated gear group， the scuffing performance test is carried out in groups on the gear contact fatigue tester. At the same time， the helix curve of the test gears detected by the gear measuring center D80 is used to accurately calculate the gluing area and the depth of the gluing groove mark. The results show that， under the same operating conditions， the loading torque of the phosphated gear is much greater than that of the unphosphorized gear， and the operating time of the phosphated gear is much more than that of the unphosphorized gear. It is concluded that， phosphating can significantly improve the anti scuffing performance of gears.